Internal standardization and least-squares background correction in high-resolution continuum source flame atomic absorption spectrometry to eliminate interferences on determination of Pb in phosphoric acid - Raposo, Jorge L. [UNESP]; Oliveira, Silvana R. [UNESP]; Nobrega, Joaquim A.; Gomes Neto, José Anchieta [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
In this work the least-squares background correction (LSBC) and internal standardization (IS) techniques were combined to eliminate spectral and transport interferences in the determination of Pb in phosphoric acid by high-resolution continuum source atomic absorption spectrometry (HR-CS AAS). Blanks, samples and reference solutions [0.10-1.00 mg L-1 Ph in 1% (v/v) HNO3] were spiked with 4.00 mg L-1 Co used as internal standard. For absorbance measurements at the wavelength integrated absorbance equivalent to 9 pixels, correlations between the ratio of absorbance of Ph to absorbance of Co and the analyte concentration were close to 0.9992. Relative standard deviations of measurements varied from 0.6 to 4% and 1 to 7% (n = 12) without and with IS/LSBC techniques, respectively. Recoveries for Ph spikes were in the 96-104% and 76-180% range with and without IS/LSBC, respectively. The limit of detection improved with IS/LSBC techniques. Accuracy of the proposed method was checked for the determinations of Ph in commercial phosphoric acid samples and results obtained with IS were better than those without IS. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Lead; Phosphoric acid; Least Least-squares background correction; Internal standardization; High-resolution continuum source atomic; absorption spectrometry